Pentingnya Profesionalisme Guru dalam Membentuk Karakter Peserta Didik - Kurniawati, Kurniawati; Maulida, Zeni Latifalul; Najib, M. Akhsan; Soraya, Siti Zazak (TAMADDUN: Jurnal Ilmu Sosial, Seni, dan Humaniora, 2025)
This study aims to examine the role of teacher professionalism in shaping the character of students in elementary school environments. Professional teachers are expected to be able to integrate pedagogical, personality, social, and professional competencies in the learning process in order to instill character values ​​such as responsibility, discipline, honesty, and caring. This study uses a qualitative descriptive method with a literature study approach sourced from books, scientific articles, journals, and related education policies. The results of the study indicate that increasing teacher professionalism contributes significantly to the success of character education. Teachers who are able to be role models, implement contextual learning, and create a positive learning environment have proven effective in shaping students' character. Therefore, strengthening teacher competence and integrity needs to be the main focus in efforts to improve the quality of national education.